STUDI PERDAGANGAN ANAK PEREMPUAN DI KECAMATAN BONGAS, KABUPATEN INDRAMAYU - , WINDIA SARI SUNARDIYANA, Agus Joko Pitoyo, S.Si, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Human trafficking is a complex issued and has no precise solution to overcome down to date. Majority over the victims are the under-ages girl which donât have their rights as a child. This research was aimed to identify factors effected those girls easily trapped in trraficking, trafficking mechanism and violence experienced throughout trafficking. The qualitative method was used in this research. Triangulation analysis intended to determine data validity. Subsequently all the data reduced to conclude. This research showed that low of education inflicts these girls to easily trap. Low motivation of study caused by the low levels of parental education, family and surrounding communities were also contribute. Economic problem was the other trigger. The girls have obligation to help their family economic with the result they were indebted and deceit by the panders. But not all the girls have the same trafficking mechanism. Overall, sexual violance was the most frequently experienced by the victims because the girls under 18 mostly working as sex worker